1998
DOI: 10.1002/(sici)1097-0185(199802)250:2<136::aid-ar2>3.0.co;2-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of mineralization indices of modeling and remodeling over eight months in middiaphyseal cross sections of femurs from adult swine

Abstract: At least 50% of the cross-sectional area from alternate anatomical subsections must be measured to predict > 90% of variation in periosteal, intracortical, and endocortical mineralizing surface and mineral apposition rate in the sow middiaphyseal femur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Double‐labeling vital stains have been extensively used to study growing long bones (Iwaniec and Crenshaw,1998; Lerner et al,1998) and occasionally sutures (Engström et al,1986; Parr et al,1997; Rafferty and Herring,1999). The five‐day interval produced good separation of the labels in the younger pigs, but in the slower growing sutures of older pigs, the labels were often superimposed.…”
Section: Discussionmentioning
confidence: 99%
“…Double‐labeling vital stains have been extensively used to study growing long bones (Iwaniec and Crenshaw,1998; Lerner et al,1998) and occasionally sutures (Engström et al,1986; Parr et al,1997; Rafferty and Herring,1999). The five‐day interval produced good separation of the labels in the younger pigs, but in the slower growing sutures of older pigs, the labels were often superimposed.…”
Section: Discussionmentioning
confidence: 99%
“…In general, emission spectra of tetracyclines are in the yellow range (dimethyltin dichloride [DMTC] being orange-yellow), xylenol orange fluoresces orange, calcein green fluoresces green, both calcein blue and 1,2-bis (2-aminophenoxy)ethane-N,N,N,N-tetraacetate (BAPTA) emit blue light, and alizarin red=complexone, procion H8-B, and hematoporphyrin are seen in the red spectrum. In the group of tetracyclines, at least 10 different types were described and used in a variety of species, such as amphibians, 42 mice, 43,44 rats, 41,45-49 guinea pigs, 50 rabbits, 14,39,51,52 (mini) pigs, 53,54 dogs, [55][56][57][58] sheep, 59-61 goats, 62-65 horses, 66 monkeys, 37 and man. 5,31,67,68 The label width is the result of bone mineralization rate multiplied by the period of time during which the labeled calcium is present in the extracellular fluid and is affected by the route of administration, the label clearance, and calcium affinity.…”
Section: Fluorochrome Choicementioning
confidence: 99%
“…Pigs appear to be more suitable than rodents for investigating the effects of nutritional factors on the skeleton, since bone remodeling occurs in pigs (Iwaniec and Crenshaw 1998) but not in rodents. Moreover, recent data have shown that porcine bone marrow contains large numbers of osteoclast progenitors (Galvin et al 1996;Scheven et al 1998;Denis et al 2000;Rassi et al 2002).…”
Section: Introductionmentioning
confidence: 99%